Report on the current research programme "Biomedicine in Africa" - DOI: 10.3395/reciis.v2i1.126en - Richard Rottenburg; René Gerrets (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2008)
This research programme examines how the science and practice of biomedicine is shaped through its engagements in various African contexts. We regard biomedicine as a circulating set of technologies, practices, and ideas that - as a by-product of prevention and healing - links individual bodies to the political order. We take Africa to be central for understanding global shifts in the making of bodies and subjectivities as well as of social, political, and juridical forms of governance exactly because the continent is so marginalised in the global political economy and thus represents a site of intense conflict and experimentation. Sociologists and anthropologists of medicine have begun to scrutinise biomedicine through studies of laboratory and clinical life in the West. There has, however, been little scrutiny of biomedicine on the more difficult terrains of non-Western countries where humanitarian crises and complex emergencies involving refugees, wars, and epidemics are common. Our programme, which focuses regionally on Ivory Coast, Kenya, Tanzania, Angola, and South Africa, aims to fill this gap.